The British police - Lawrence, Paul (2014)
[About the book] The Encyclopedia of Criminology and Criminal Justice is an international, comprehensive reference tool for the field of Criminology and Criminal Justice that is both cutting edge as well as of very high scientific quality and prestige. This 10-volume work provides a complete and systematic coverage of the field that is unprecedented. The Encyclopedia "defines the field" through its choice of organization and entries. It identifies and brings emerging ideas and trends to the forefront. The Encyclopedia covers Criminology and Criminal Justice in ten broad areas, with leading researchers writing substantive contributions within their area of expertis